2010
DOI: 10.1038/cr.2010.163
|View full text |Cite
|
Sign up to set email alerts
|

Direct differentiation of atrial and ventricular myocytes from human embryonic stem cells by alternating retinoid signals

Abstract: Although myocyte cell transplantation studies have suggested a promising therapeutic potential for myocardial infarction, a major obstacle to the development of clinical therapies for myocardial repair is the difficulties associated with obtaining relatively homogeneous ventricular myocytes for transplantation. Human embryonic stem cells (hESCs) are a promising source of cardiomyocytes. Here we report that retinoid signaling regulates the fate specification of atrial versus ventricular myocytes during cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
293
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(314 citation statements)
references
References 39 publications
19
293
2
Order By: Relevance
“…This model system provides unique opportunities to study the molecular pathways that control cardiac lineage commitment and cell fate specification. In recent years, the ability to efficiently generate cardiomyogenic cells from hPSCs has greatly improved [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] . However, among protocols there is cell line variation with respect to the efficiency in generating cardiomyogenic cells and timing at which the cells express chamber-specific markers (e.g., ventricle and atria).…”
Section: Introductionmentioning
confidence: 99%
“…This model system provides unique opportunities to study the molecular pathways that control cardiac lineage commitment and cell fate specification. In recent years, the ability to efficiently generate cardiomyogenic cells from hPSCs has greatly improved [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] . However, among protocols there is cell line variation with respect to the efficiency in generating cardiomyogenic cells and timing at which the cells express chamber-specific markers (e.g., ventricle and atria).…”
Section: Introductionmentioning
confidence: 99%
“…The sole work in the literature demonstrating this attempt was Zhang et al who demonstrated direct differentiation of ESC toward atrial and ventricular myocyte fate [302]. In this report, myocyte while the treated culture with retinoic acid specified CM differentiation to atrial like myocyte.…”
Section: Directed Culture Of Ipscs Towards An Atrial or Ventricular Lmentioning
confidence: 75%
“…This approach was founded on evidence that retinoic acid regulates anterior posteriorpolarization of the heart and expression of atrial specific genes [302,278,286]. In a …”
Section: Directed Differentiation Of L-epc-ipscs Into Atrial Myocytesmentioning
confidence: 99%
“…This was possible thanks to (1) generation of induced pluripotent stem cells (iPSCs) from somatic cells of the patient and (2) optimization of in vitro differentiation of iPSCs into cardiomyocytes (CMs) [1]. Currently, we are able to derive human chamber-specific CMs using robust and highly efficient protocols [2][3][4]. Although these cells are capable of spontaneous beating and show many physiological features of CMs, they remain immature.…”
Section: Introductionmentioning
confidence: 99%